A seated virtual exercise program to improve cardiovascular function in adults with chronic neurological impairments: a randomized controlled trial - Devina S. Kumar; Devina S. Kumar; Amy Bialek; Ayushi A. Divecha; Rachel M. Garn; Lydia E. J. Currie; Kathleen M. Friel; Kathleen M. Friel (Frontiers in Rehabilitation Sciences)
BackgroundIndividuals with chronic neurological impairments often face significant barriers to regular exercise such as limited access to facilities, transportation challenges, and safety concerns. Tele-exercise has emerged as a potential solution to these challenges, particularly in the context of the COVID-19 pandemic. This study aimed to investigate the effects of a seated home-based tele-exercise regimen on cardiovascular function in adults with chronic neurological impairments.MethodsIn this virtual randomized controlled trial, 63 participants with Chronic Neurological Impairments were randomized into either a synchronous group that attended live online exercise sessions via Zoom, or an asynchronous group that accessed pre-recorded exercise sessions. Both groups completed three 45 min sessions per week focused on moderate to high-intensity seated exercises over 12 weeks. Primary outcomes including Heart Rate (HR) Recovery (HRR), HR at Rest (HR Rest) and HR at peak exercise (HR Max) were averaged across three sessions at baseline, mid-study, and end of study. Secondary outcomes, including satisfaction with the equipment and virtual format were assessed using custom-designed surveys, while exercise motivation, enjoyment, and quality of life were measured using standardized instruments.ResultsThe analysis of HRR across the pre (p = 0.57), mid (p = 0.7), and post time points (p = 0.61) revealed no statistically significant differences between the synchronous and asynchronous groups. HR Rest and HR Max did not change over time. The synchronous group showed higher exercise motivation compared to the asynchronous group (p = 0.0001). Satisfaction with the virtual format was high, with 90% of participants reporting satisfaction with the use of the Polar heart rate monitor and 84% with Zoom.ConclusionWhile no significant cardiovascular improvements were observed, the study highlights the feasibility of a virtual, seated exercise program for individuals with chronic neurological impairments. The higher reported exercise motivation in the synchronous group suggests that live, interactive sessions may be more engaging for participants. These findings underscore the potential of tele-exercise programs to provide accessible, home-based interventions, though further research is necessary to assess their long-term impact on cardiovascular health and overall well-being. Clinical Trial Registrationidentifier (NCT04564495).